Administrative Empowerment among Academic Leaders and its Relationship to the Quality of Work Life of Faculty Members - Darawsheh , Najwa Abdel Hamid; Alrashdan, Hanadi; Alzawaideh, Mohammad; Ajouly, Thaer; almheiri, Abdulla sultan bin Hareb; Aldarmaki, Ibrahim Abdelrahman Eisa (Journal of Ecohumanism, 2024)
The current study aimed to reveal the degree to which academic leaders practice administrative empowerment in Jordanian universitiesin Irbid Governorate, and show the quality level of work life of faculty members and the relationship between them. The study adopted the survey correlated method, and the sample consisted of (307) member staff. To achieve the study objectives, the electronic questionnaire was used as the study tool. The results showed that thedegree to which academic leaders practice administrative empowerment came with a moderate degree and the level of quality work life of faculty members came with a high degree. The study results also showed a strong relationship between administrative empowerment and the quality of work life. In light of the results, the researchers recommended encouraging academic leaders to accept the idea of digital empowerment through enhancing the participation methods in taking university decisions.